Parent–Teacher Synergy in Guiding Student Development in Majene Regency, Indonesia - Mithhar Mithhar; Asri Astria; Evy Segarawati Ampry (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Student development is a multidimensional process shaped by the interaction between family, school, and the wider social environment. This article aims to analyze parent–teacher synergy in guiding student development in Majene Regency, West Sulawesi, Indonesia. This study employed a qualitative research method. The research was conducted over three months, from January to March 2026, involving 10 purposively selected informants, including school leaders, the vice principal for student affairs, a homeroom teacher, a subject teacher, a guidance and counseling teacher, a school committee representative, parents, and a student. Data were collected through interviews, literature review, and documentation, and analyzed using descriptive qualitative methods, including data reduction, thematic categorization, and interpretation. The findings show that parent–teacher synergy plays an important role in strengthening students’ motivation to learn, discipline, character development, academic engagement, self-confidence, and social-emotional development. This synergy is realized through regular communication, parental involvement in school programs, collaborative monitoring of academic and non-academic progress, alignment of educational values, and ethical use of communication technology. The article concludes that parent–teacher synergy is a fundamental basis for creating a holistic, consistent, and sustainable educational environment.